Motion-Genetic Testing is Useful in the Diagnosis of Nonhereditary Pancreatic Conditions: Arguments Against the Motion - Jonathan A Cohn (Canadian Journal of Gastroenterology)
Mutations of two genes, the cystic fibrosis transmembrane conductance regulator gene (CFTR) and the pancreatic secretory trypsin inhibitor gene (PSTI), are associated with an increase in the risk of idiopathic chronic pancreatitis. Persons who have mutations of both CFTR alleles (one severely and one mildly affected) are especially susceptible to this disease. Because these compound heterozygotes have sufficient residual CFTR function, they do not develop cystic fibrosis lung disease. One PSTI mutation, N34S, independently increases the risk of pancreatitis. Thus, the risk of pancreatitis is greatest among individuals who are CFTR compound heterozygotes and who also have the PSTI mutation. Nonetheless, most people with CFTR and PSTI mutations do not develop pancreatitis. This fact indicates that environmental influences and gene-gene interactions also affect pancreatitis risk. Although CFTR and PSTI genetic testing can identify persons at an increased risk of pancreatitis, there are several reasons why the routine screening of individuals with nonhereditary pancreatitis is not recommended at this time: most disease-associated mutations are not detected by readily available techniques, genetic counselling guidelines do not exist, most patients with mutations do not develop pancreatitis and the results of testing do not affect the clinical management of pancreatitis.